Teachers’ and Parents’ Views On 60-66 Month Old Children’s Entrance to First Grade - Serkan Demir; Elif Üstün (Elementary Education Online, 2023)
The aim of this study is to find out the views of parents who registered their children for the first grade and views of first grade teachers who teach 60-66-month-old students in the first year of this practice.Whilethestudy is designed as qualitative, a kind of singlecasestudyapproach is usedwith a group of 32 first-gradeteachersand 30 parents in the İstanbul City.Data were gathered through the interview technique. Data was collected through a semi-structured interview form which was developed by the researchers. The most important factor which led the parents to register their 60-66-month-old children for the first grade earlier was that they were informed of the fact that the first grade curriculum would be developed considering the developmental features of 60-66-month-old children. According to teachers’ observations, 60-66-month-old children are reluctant and have problems learning the letters in the reading stage.